Author Correction: Synuclein and dopamine: the Bonnie and Clyde of Parkinson's disease. (July 2018) - Roy, Subhojit
In the version of this article initially published, the molecular mass of synuclein was given as 140 kDa instead of ~14 kDa. The error has been corrected in the HTML and PDF versions of the article.